Assessment of the Implementation of 2007 Public Procurement Acts in Service Delivery of National Insurance Commission, Abuja - Augutine, Augustina; Aliegba , Becky Ade; Amehojo , Daniel (Kashere Journal of Politics and International Relations, 2024)
The public procurement Act (PPA) is a critical legislative instrument designed to promote transparency, efficiency and accountability in the procurement process across Nigerian public institutions. This study assesses the influence of adherence to the 2007 Public Procurement Act on the accountability mechanisms within the National Insurance Commission (NAICOM) in Abuja. The population of the study is 267 of which sample of 100 was taken; simple percentage tool of analysis was adopted. The study objectives are to assess the influence of adherence to the 2007 Public Procurement Act on the accountability mechanisms within the National Insurance Commission (NAICOM) in Abuja and to evaluate the extent to which the implementation of the 2007 Public Procurement Act contributes to achieving value for money in the procurement processes of the National Insurance Commission (NAICOM) in Abuja. The study used likert scale closed – ended (fixed-alternative) questions that required strongly agree, agree, undecided, disagree, and strongly disagree. The study adopted survey and documentary research design methods. The study relied on both primary and secondary sources of data. The study gathered quantitative data through structured questionnaire distributed to employees at various levels within the NAICOM who are involved in the supervision of insurance industries. The study revealed that the implementation of the 2007 Public Procurement Act significantly contributes to achieving value for money in the procurement processes of the National Insurance Commission (NAICOM) in Abuja.